New Directions in the History of the Novel
XII, 244 p.
Keywords: New Directions in the History of the Novel challenges received views of literary history and sets out new areas for research. A re-examination of the nature of prose fiction in English and its study from the Renaissance to the 21st century, it will become required reading for teachers and students of the novel and its history.